2013
DOI: 10.3892/ijo.2013.2026
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between p38 and Smad3 through TGF-β1 in JEG-3 choriocarcinoma cells

Abstract: Abstract. Choriocarcinoma is a highly malignant trophoblastic tumor related to pregnancy that often occurs with a complete hydatidiform mole. It grows quickly and can also widely metastasize to other organs or tissues through both the venous and lymphatic systems. The transforming growth factor-β1 (TGF-β1) belongs to a growth factor superfamily and has been suggested to play a critical role in regulating the genesis and development of choriocarcinoma through a variety of Smad-independent pathways, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In addition, we found that miR-891b overexpression or Cbl-b knockdown increased the expression of Smad3 protein. In choriocarcinoma cells, the expression of Smad3 could be promoted by TGF-β1, and suppressed by p38 MAPK inhibitor [29]. In the present study, Smad3 mRNA level was increased by miR-891b overexpression or Cbl-b knockdown.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, we found that miR-891b overexpression or Cbl-b knockdown increased the expression of Smad3 protein. In choriocarcinoma cells, the expression of Smad3 could be promoted by TGF-β1, and suppressed by p38 MAPK inhibitor [29]. In the present study, Smad3 mRNA level was increased by miR-891b overexpression or Cbl-b knockdown.…”
Section: Discussionsupporting
confidence: 49%
“…Following this, 5 ng/ml TGF-β1 was added into each well, except those of the control group, and incubation was continued for 2 h. Previous results from our laboratory indicated that p38 MAPK inhibitors can attenuate TGF-β1-induced Smad3 protein expression (21); thus; we further examined the effect of p38 inhibitors on the transcriptional levels of Smad3 in response to TGF-β1. Compared with the control group, the mRNA expression levels of Smad3 were significantly elevated in TGF-β1 group (P<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that blocking the TGF-β pathway by using a TGF-β receptor inhibitor significantly reduces the expression levels of p38 and phospho-p38 in JEG-3 cells. Additionally, treatment of JEG-3 cells with a p38 MAPK inhibitor (SB 203580) attenuated TGF-β1-induced Smad3 protein expression and suppressed the activation of Smad3 (21). These results suggested that there is crosstalk between p38 MAPK and Smad3 through TGF-β signaling in human choriocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that vitamin D and its derivatives can induce the expression of bone morphogenetic protein (BMP) and activate the BMP-Smad signaling pathway (39). The BMP-Smad signaling pathway is involved in the pathway for enzyme-coupled receptor signal transduction, and BMP is one β-tumor necrosis factor (38,40) that regulates cell proliferation, differentiation and apoptosis. Furthermore, previous in vitro experiments demonstrated that vitamin D and its metabolites or analogs induce BMP overexpression and activates BMP-Smad signaling pathway to suppress the development of colon cancer (41,42).…”
Section: % CI ----------------------------------------------mentioning
confidence: 99%